Values, attitudes and economic behavior - Michael W. M. Roos (RWI - Leibniz-Institut für Wirtschaftsforschung, 2018)
In this paper, I propose a simple model in which behavior is determined by the individual's attitude towards the behavior and the attitude depends on the individual's values. The model is based on the Schwartz theory of human values, which is very prominent in social psychology. Values are desirable, transsituational, abstract goals. In the model, they fix aspiration levels for specific targets that are related to an object. The distance between the properties of an object and the aspiration levels determines the degree of the agent's satisfaction or dissatisfaction with the properties of the object. Attitude is the importance-weighted sum of the degrees of (dis-)satisfaction. The model highlights the importance of systematic and measurable heterogeneity among individuals and shows how values can predict differences in tastes and sensitivity to income and prices. The model also explains when Veblen effects occur. – – In diesem Papier stelle ich ein einfaches Modell vor, in dem das Verhalten eines Individuums durch seine Einstellung gegenüber diesem Verhalten bestimmt wird und die Einstellung von den Werten des Individuums abhängt. Das Modell basiert auf der Werte-Theorie von Schwartz, die in der Sozialpsychologie sehr bedeutend ist. Werte sind wünschenswerte, transsituationale, abstrakte Ziele. Im Modell legen sie Aspirationsniveaus für spezifische Ziele fest, die mit einem Objekt verbunden sind. Die Distanz zwischen den Eigenschaften eines Objekts und den Aspirationsniveaus bestimmt den Zufriedenheitsgrad eines Individuums mit den Objekteigenschaften. Die Einstellung ist die nach Wichtigkeit gewichtete Summe der (Un-)Zufriedenheitsgrade. Das Modell betont die Bedeutung systematischer und messbarer Heterogenität unter Individuen und zeigt, wie Werte Unterschiede in Vorlieben und Einkommens- und Preissensitivitäten vorhersagen können. Das Modell erklärt auch, wann Veblen-Effekte auftreten.
Keywords: D01; D11; D91; 330; values; attitudes; heterogeneity; Veblen effect; preferences; multiple attributes